Effect of Postural Changes on Leg Muscle Tone and Arterial Blood Pressure in Able‑Bodied People and People after Chronic Spinal Cord Injury (Baltic Journal of Sport and Health Sciences, 2011)
Research  background  and  hypothesis.  Following  spinal  cord  injury  part  of  sympathetic  nervous  system is  disrupted  from  the  brain  stem  control,  which  results  in  cardiovascular  system  regulation  disorders.  Impaired cardiovascular regulation may cause orthostatic hypotension or other negative impacts on persons’ health. However, there are adaptive mechanisms which may change cardiovascular regulation and compensate these cardiovascular disorders. One of the mechanisms that may affect the occurrence of orthostatic hypotension may be changes in muscle tone after spinal cord injury.The aim of research was to ascertain the effect of muscle tone changes on blood pressure in persons with spinal cord injury through ortho-clinostatic test.Research methods. During passive ortho-clinostatic test, non-invasive blood pressure was continuously measured using the vital signs tracking monitor and leg muscle tone measurement was performed using myotonometer.Research results. In control group muscle tone is characterized as constant wave – it decreases in orthostasis and increases in clinostasis. In paraplegic group muscle tone changes are as similar to those in controls, except that dynamics is not so constant and numeric values are lower. In tetraplegics we can see that muscle tone changes rapidly and tone in thigh muscles has a tendency to decrease through all the test. Discusion and conclusions: 1. Leg muscle tone changes are important for blood pressure compensating mechanisms when the body position changes: it increases during orthostasis and decreases during clinostasis.2.  Blood  pressure  varies  differently  among  able-bodied  persons  and  persons  with  spinal  cord  injury.  The degree of the breach has a significant impact on the occurrence of compensatory peripheral regulation mechanisms. Characteristics  of  blood  pressure  fluctuations  during  body  position  changes  in  paraplegics  are  similar  to  those of reactions as in the able-bodied controls, while in tetraplegia case, possibilities of homeostatic blood pressure compensation during body posture changes are significantly reduced.Keywords: blood pressure, muscle tone, paraplegia, tetraplegia.